PENGARUH DISIPLIN KERJA, KOMPETENSI, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BULELENG - Widi Widya Sari, Ni Luh Ayu; Sri Kasih, Ni Luh (Komunitas Manajemen Kompetitif, 2024)
The purpose of this study was to determine the effect of Work Discipline, Competence, and Work Motivation on Employee Performance. This research was conducted at the Office of the Population and Civil Registration Office of Buleleng Regency. The data collection technique used was the Questionnaire technique. The sample taken in this study was 70 respondents using certain criteria. The data analysis techniques used are Validity and Reliability Test, Classical Assumption Test, Multiple Linear Analysis Test, and Coefficient of Determination. Model testing used is the T Test and F Test. The results showed, 1) Work Discipline has a positive and significant effect on Employee Performance which is indicated by the t value of 3.012> t table 1.668 with a significance value of 0.004 <0.05, 2) Competence has a positive and significant effect on employee performance which is indicated by the t value of 2.036> t table 1,668 with a significance value of 0.046 < 0.05, 3) Work Motivation has a persial effect on employee performance with a t value of 2.619> t table 1,668 with a significance value of 0.011 < 0.05, 4) Work Discipline, Competence, and Work Motivation simultaneously have a positive and significant effect on Employee Performance as indicated by the Fcount value of (70,804)> f table of (2,744) with an F test significance value of 0.000 which is smaller than ɑ = 0.05 and the influence of the Work Discipline, Competence and Work Motivation variables as indicated by the Coefficient of Determination of 0.752 or 75.2% while the remaining 24.8% is influenced by other variables outside this study.